2014
DOI: 10.1097/ccm.0b013e3182a27413
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Emergency Team Call

Abstract: Implementation of a rapid-response system was associated with an increase in do-not-resuscitate order placement. As a sentinel event, medical emergency team activation and transfer to a critical care unit foster consideration of goals of care and frequently results in a transition to a palliative care strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Two recent studies analyzed the importance of RRTs in providing goals-of-care discussions [24,25]. Both studies found that approximately one third of RRT activations were associated with end-of-life issues or questions about limitations of medical care, indicating that provision of these discussions is an important function of the RRS.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies analyzed the importance of RRTs in providing goals-of-care discussions [24,25]. Both studies found that approximately one third of RRT activations were associated with end-of-life issues or questions about limitations of medical care, indicating that provision of these discussions is an important function of the RRS.…”
Section: Discussionmentioning
confidence: 99%
“…Vasquez et al (8) found that implementation of the RRT increased formal comfort care orders, administration of opioids and chaplain visits. Smith et al (17) found that the implementation of RRTs increased the trend of do-not-resuscitate orders without impacting hospital mortality. An analysis of RRTs and EOL status from the MERIT study found that approximately 8% of RRT calls resulted in a change of EOL status (6).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study [10], 45 ward patients with a DNR order in place were reviewed by the MET and 18 (40%) were transferred to the ICU after MET activation.…”
Section: Measures Of Effectivenessmentioning
confidence: 99%